Analysis of the Effect of the Surface Inclination Angle on the Roughness of Polymeric Parts Obtained with Fused Filament Fabrication Technology - Martín-Fernández, Francisco de Sales; Martín-Sánchez, María Jesús (IOAP-MDPI, 2023)
The aim of this work was to conduct a dimensional study, in terms of microgeometry, using parts from an additive manufacturing process with fused filament fabrication (FFF) technology. As in most cases of additive manufacturing processes, curved surfaces were obtained via approximation of planes with different inclinations. The focus of this experimental study was to analyze the surface roughness of curve geometry from surface-roughness measurements of the plane surfaces that generate it. Three relevant manufacturing parameters were considered: layer height, nozzle diameter and material. Taguchi’s experimental design based on the Latin square was applied to optimize the set of specimens used. For the manufactured samples, the surface-roughness parameters Ra (roughness average), Rq (root mean square roughness) and Rz (maximum height) were obtained in eight planes of different inclinations (0° to 90°). The results were analyzed using both a graphical model and an analysis of variance study (ANOVA), demonstrating the dependency relationships among the parameters considered and surface finish. The best surface roughness was reached at 85°, with a global average Ra value of 8.66 µm, increasing the average Ra value from 6.39 µm to 11.57 µm according to the layer height increase or decreasing it slightly, from 8.91 µm to 8.41 µm, in relation to the nozzle diameter increase. On the contrary, the worst surface roughness occurred at 20°, with a global average Ra value of 19.05 µm. Additionally, the theoretical profiles and those from the surface-roughness measurement were found to coincide greatly. Eventually, the eight regression curves from the ANOVA allowed prediction of outputs from future specimens tested under different conditions.
Keywords: Taguchi, Métodos de (Control de calidad); Additive manufacturing; Fused filament fabrication; Surface roughness; Thermoplastic polymers; ANOVA; Taguchi